LncRNA LINC00857 regulates the progression and glycolysis in ovarian cancer by modulating the Hippo signaling pathway. (12th September 2020) - Lin, Xueke; Feng, Dilu; Li, Ping; Lv, Yuchun
Abstract: Ovarian cancer is one of the most common gynecological cancers with high morbidity and mortality, which seriously endangers women's health and quality of life. Long noncoding RNAs (lncRNAs) can regulate the progression of cancers, including ovarian cancer. LINC00857 (long intergenic non‐protein coding RNA 857) has been discovered to be a crucial factor in the regulation of cancer development. Nevertheless, the specific functions and mechanisms of LINC00857 in ovarian cancer remain unclear. The Hippo signaling pathway can involve in cancer progression. In our research, we aimed to investigate the correlation of LINC00857 and Hippo pathway. Quantitative real‐time polymerase chain reaction assay was utilized to test the expression of LINC00857 in ovarian cancer tissues and cells. Functional experiments revealed that LINC00857 silencing led to the inhibition on cell proliferation, migration, invasion, and glycolysis but accelerated cell apoptosis in ovarian cancer. Mechanism experiments, including RNA immunoprecipitation, RNA pull‐down, and luciferase reporter experiments demonstrated that LINC00857 could regulate YAP1 (Yes1 associated transcriptional regulator) by competitively binding to miR‐486‐5p in ovarian cancer. In a word, this study unveiled that LINC00857 regulates YAP1 by competitively binding to miR‐486‐5p and accelerates ovarian cancer progression. Abstract : MiR‐486‐5p restrains cell progression and promotes cell apoptosis in ovarian cancer. Long intergenic non‐protein coding RNA 857 accelerates ovarian cancer progression and glycolysis via regulating Yes1 associated transcriptional regulator.